Post-Brexit back-shoring strategies: what UK manufacturing companies could learn from the past? - Moradlou, Hamid; Fratocchi, Luciano; Skipworth, Heather; Ghadge, Abhijeet (Taylor and Francis, 2021)
The manufacturing sector in the UK is currently undergoing a significant supply chain transformation and managers are re-evaluating supply chain location decisions to minimise the disruptions caused by Brexit. This entails manufacturing offshoring and back-shoring once again being considered as strategic decisions and companies ought to make informed choices with respect to where they source or manufacture their products. This paper aims to contribute to an improved understanding of the back-shoring phenomenon in the UK. Eight case studies of back-shoring have been analysed and compared using a theoretically informed framework. The results show that back-shoring can stem from both misjudgements of previous offshoring decisions as well as changes in the demand pattern in the home country. Unlike offshoring decisions being mainly cost-oriented, strategic shift aimed at increasing the value perceived by the customer has a pivotal role in the back-shoring decision. Furthermore, skill shortage is the main barrier for the implementation of back-shoring strategies in the UK and requires companies’ attention prior to its repatriation.
Keywords: Brexit; re-shoring; Back-shoring; Offshoring